Effect of the corner angle on spring-back deformation for unidirectional L-shaped laminate composites manufactured through autoclave processing - Mohd Nasir, Mohd Nazreen; Seman, Mh Adam; Mezeix, Laurent; Aminanda, Yulfian; Rivai, Ahmad; Ali, Karim M. (Asian Research Publishing Network (ARPN), 2016)
The residual stresses that develop within fibre-reinforced laminate composites during autoclave processing lead to dimensional warpage known as spring-back deformation. A number of experiments have been conducted on flat laminate composites with unidirectional fibre orientation to examine the effects of both the intrinsic and extrinsic parameters on the warpage. This paper extends the study on to the corner angle effect on spring-back for L-shaped laminate composites. Tools with corner angles of 30o, 45o and 90o were fabricated and its influence on the magnitude and final deformation shape of unidirectional L-shaped laminates were observed. Essentially, the experimental results proved that the corner angle parameter has a significant impact on spring-back deformation